2002
DOI: 10.1007/bf03165138
|View full text |Cite
|
Sign up to set email alerts
|

The therapy of myelofibrosis: Targeting pathogenesis

Abstract: Myelofibrosis with myeloid metaplasia (MMM) encompasses the diagnoses of agnogenic myeloid metaplasia (idiopathic myelofibrosis), as well as the advanced phases of polycythemia vera and essential thrombocythemia (post polycythemic and post thrombocythemia myeloid metaplasia, respectively). MMM is a clonal, hematopoietic stem cell disorder in which neither the pathogenesis, nor a broadly applicable effective therapy have been described. Clinically, these patients experience progressive marrow replacement by fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Currently, no chemotherapeutic agent has been demonstrated to prolong the survival in this disease, although supportive care with transfusions or treatment with HU, interferon, danazol, or thalidomide may improve the symptoms and possibly improve the quality of life of these patients. 1, [8][9][10][11] Allogeneic bone marrow transplantation, however, is the only curative treatment that by means of the administration of radio/chemotherapy agents, or a graft-versus-tumor effect elicited by donor lymphocytes, is capable of reducing the tumor burden. Nevertheless, previous studies have shown that fully myeloablative preparative regimens, with or without total body irradiation, lead to a transplant-related mortality in 27% to 48% of the patients (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, no chemotherapeutic agent has been demonstrated to prolong the survival in this disease, although supportive care with transfusions or treatment with HU, interferon, danazol, or thalidomide may improve the symptoms and possibly improve the quality of life of these patients. 1, [8][9][10][11] Allogeneic bone marrow transplantation, however, is the only curative treatment that by means of the administration of radio/chemotherapy agents, or a graft-versus-tumor effect elicited by donor lymphocytes, is capable of reducing the tumor burden. Nevertheless, previous studies have shown that fully myeloablative preparative regimens, with or without total body irradiation, lead to a transplant-related mortality in 27% to 48% of the patients (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Nevertheless, the use of fully myeloablative conditioning regimens has been shown to be associated with a high transplantation-related mortality (TRM) rate, 13-16 especially in advanced and elderly patients. In particular, patients older than 45 years were previously reported to have a significantly worse probability of survival compared with younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…The bone marrow reaction is thought to be reactive and cytokine mediated. It has been hypothesized that long-term presence of profibrotic cytokines released from these abnormal cells are capable of inducing irreversible changes in bone marrow stromal cells and the extracellular matrix, leading to bone marrow fibrosis and consequently hematological failure [2,3]. Although the etiopathogenesis of this profound stromal reaction remains equivocal, mediating cytokines such as transforming growth factor-beta 1 (TGF-β 1 ) are believed to be produced by clonal megakaryocytes, monocyte-macrophage cell lineage, or both [4].…”
Section: Introductionmentioning
confidence: 99%